Resveratrol alleviates acute lung injury in mice by promoting Pink1/Parkin-related mitophagy and inhibiting NLRP3 inflammasome activation - Wu, Dongdong; Zhang, Hui; Li, Fang; Liu, Shuai; Wang, Yang; Zhang, Zhao; Wang, Jiannan; Wu, Qiuge (Biochimica et biophysica acta. General subjects, 2024)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are characterized by rapid onset and widespread inflammation in the lungs, often leading to respiratory failure. These conditions can be triggered by various factors, resulting in a severe inflammatory response within the lungs. Resveratrol, a polyphenolic compound found in grapes and peanuts, is renowned for its potent antioxidative and anti-inflammatory properties. In this study, we investigated how resveratrol protects against lipopolysaccharide (LPS)-induced ALI in mice. We established mouse models of LPS-induced ALI and inflammation in bronchoalveolar lavage fluid (BALF) macrophages. Through histopathological examination, immunofluorescence, western blot, enzyme-linked immunosorbent assay (ELISA), and transmission electron microscopy (TEM), we assessed the impact of resveratrol on the activation of NOD-like receptor thermal protein domain-associated protein 3 (NLRP3) inflammasomes and the process of mitophagy. Our findings indicate that resveratrol significantly mitigated the lung injury and inflammation caused by LPS. This was achieved by inhibiting the oligomerization of apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) and the activation of NLRP3 inflammasomes. Resveratrol also reduced the levels of IL-1β and IL-18 in serum and BALF, decreased caspase-1 expression, and diminished macrophage pyroptosis. Furthermore, it upregulated Pink1, Parkin, Beclin-1, Autophagy-Related 5 (Atg5), and Microtubule-Associated Proteins 1 A/1B Light Chain 3B (LC3B-II), thereby enhancing mitophagy. Conversely, mitophagy was inhibited by Pink1 siRNA. In conclusion, resveratrol ameliorated ALI in mice, potentially by inhibiting the activation of NLRP3 inflammasomes, activating the Pink1/Parkin pathway, and promoting mitophagy. •This study highlights the protective effects of resveratrol against lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice.•We show that resveratrol reduces lung injury and inflammation by blocking NLRP3 inflammasome activation.•Resveratrol inhibits ASC oligomerization and reduces IL-1β and IL-18 cytokine release.•Additionally, it activates the Pink1/Parkin pathway and enhances mitophagy, leading to the reduction of macrophage pyroptosis.•Our findings suggest that resveratrol holds potential as a therapeutic agent against ALI and associated inflammatory conditions.